Contributions to Nephrology 2007
DOI: 10.1159/000102072
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in Sepsis- and Cardiopulmonary Bypass-Associated Acute Kidney Injury

Abstract: Acute kidney injury (AKI) is a major medical problem in critical illness, and has a separate independent effect on the risk of death. Septic shock and cardiac surgery utilizing cardiopulmonary bypass are the two most common factors contributing to AKI. Clinical predictors and biochemical markers identified for the development of AKI can only explain a part of this individual risk. Another tool to predict the risk of AKI and to improve individualized patient care focuses on the identification of genetic risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 82 publications
0
14
0
1
Order By: Relevance
“…The etiology of renal dysfunction after cardiac surgery is multifactorial, and where postoperative renal dysfunction is so severe as to require renal replacement therapy, mortality rates are as high as 63% (1,3). Several genetic polymorphisms have been identified as critical factors in the occurrence and progression of renal dysfunction after cardiac surgery with CPB (23–27). However, Tong et al (28).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of renal dysfunction after cardiac surgery is multifactorial, and where postoperative renal dysfunction is so severe as to require renal replacement therapy, mortality rates are as high as 63% (1,3). Several genetic polymorphisms have been identified as critical factors in the occurrence and progression of renal dysfunction after cardiac surgery with CPB (23–27). However, Tong et al (28).…”
Section: Discussionmentioning
confidence: 99%
“…While there have been several descriptive reviews on this topic (38,39), to the authors' knowledge this is the first systematic review of genetic determinants of AKI. In summary, it was found that there is no single polymorphism that can be conclusively described as a risk factor in AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, polymorphisms of TNF-α, IL-6, IL-10 and NADPH oxidase among others have been associated with AKI in sepsis (Haase-Fielitz et al, 2007). …”
Section: Discussionmentioning
confidence: 99%